An investigation into the management of online teaching and learning spaces: A case study involving graduate research students - Rohan Jowallah (Athabasca University Press, 2014)
This research evaluates the strategies implemented to support the research activities of postgraduate students pursuing online master’s programs in the University of the West Indies Open Campus, as well as the activities of their supervisors. The three main strategies employed were (1) the use of a web-based ‘teaching-learning space’ to facilitate asynchronous interaction between students and their supervisors; (2) the provision of a scheduling tool to facilitate the planning of one-on-one meetings via a synchronous web-conferencing tool; and (3) the organization of research seminars using the same web-conferencing tool.